Transformation of Tax Administration in Ukraine Based on Blockchain Technologies in the Context of Global Practices - O. Yu. Balazyuk; V. V. Yasyshena (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2026)
The article examines the transformation of tax administration in Ukraine based on blockchain technologies with emphasis on strengthening the accounting dimension of fiscal digitalization. The relevance of the study is determined by the need to create a transparent information environment for recording business transactions, ensuring the reliability of primary data, minimizing discrepancies between financial and tax accounting, and enhancing fiscal security as part of Ukraine's integration into the global digital space. The purpose of the study is to provide a comprehensive analysis of the theoretical and applied foundations of implementing blockchain technologies in the tax administration system, focusing on their impact on accounting organization, tax liability formation, and the digital verification of business transactions in the context of global practices. It has been established that the use of distributed ledger technology creates prerequisites for transforming primary documentation, computerizing generation of accounting entries and tax indicators through smart contracts, and forming a continuous audit trail. It is demonstrated that the integration of blockchain solutions promotes the convergence of financial and tax accounting, enhances the evidential value of accounting data, reduces the risks of manipulation of transaction dates and content, and optimizes tax control procedures. The international experience of applying blockchain technologies in tax administration, electronic document management, and integration with digital identification systems is highlighted. It is argued that a phased implementation of blockchain solutions is advisable for Ukraine, particularly in computerizing tax accounting, monitoring supply chains, and integrating tax registers with financial reporting systems.